Psychosocial precursors of the correct sanitation and sanitization of the patient unit in the hospital setting - Ricci, Federico; Aldini, Alice; Ciramini, Marlene; Gioia, Maria Grazia; Quintero, Narcisa; Ronsval, Daniela; Vecchiatini, Silvia; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Worrying data indicate the urgency of strongly limiting Healthcare-Associated Infections (HAI). Therefore, according to the Theory of Planned Behavior, the psychosocial precursors of correct sanitation and sanitization were assessed. Methods. An Italian sample of hospital health workers (nurses, healthcare assistants, cleaners; N=250), replied to a validated questionnaire measuring: a) knowledge of HAI; b) favorable attitude towards the correct sanitation and sanitization procedure; c) perception that the management and colleagues give importance to the government of infectious risk; d) perception of being able to implement risk management behaviors; e) perception of having received proper training for the prevention of HAI. Results. The results show many mistakes about knowledge, the perception of insufficient specific training, and not always favorable attitude towards sanitation and sanitization practices. Workers also perceive that they can act the required behaviors and that the management of infectious risk represents a value in the group they belong to, but they believe that the management does not offer sufficient support. Conclusions. The improvement of the factors considered (knowledge, personal attitudes, actions of management and colleagues, perception of being able to implement the required behaviors) is affected by proper training. This is one of the aspects on which management should invest more.